Labour companionship and women's experiences of mistreatment during childbirth: results from a multi-country community-based survey. (23rd November 2020) - Balde, Mamadou Dioulde; Nasiri, Khalidha; Mehrtash, Hedieh; Soumah, Anne-Marie; Bohren, Meghan A; Diallo, Boubacar Alpha; Irinyenikan, Theresa Azonima; Maung, Thae Maung; Thwin, Soe Soe; Aderoba, Adeniyi K; Vogel, Joshua P; Mon, Nwe Oo; et al.
Abstract : Background: Evidence has shown the benefits of labour companions during childbirth. Few studies have documented the relationship between the absence of labour companions and mistreatment of women during childbirth in low-income and middle-income countries using a standardised tool. Methods: We conducted a secondary analysis of the WHO multi-country study on how women are treated during childbirth, where a cross-sectional community survey was conducted with women up to 8 weeks after childbirth in Ghana, Guinea, Nigeria and Myanmar. Descriptive analysis and multivariable logistic regression were used to examine whether labour companionship was associated with various types of mistreatment. Results: Of 2672 women, about half (50.4%) reported the presence of a labour companion. Approximately half (49.6%) of these women reported that the timing of support was during labour and after childbirth and most of the labour companions (47.0%) were their family members. Across Ghana, Guinea and Nigeria, women without a labour companion were more likely to report physical abuse, non-consented medical procedures and poor communication compared with women with a labour companion. However, there were country-level variations. In Guinea, the absence of labour companionship was associated with any physical abuse, verbal abuse, or stigma or discrimination (adjusted OR (AOR) 3.6, 1.9–6.9) and non-consented vaginal examinations (AOR 3.2, 1.6–6.4). In Ghana, it was associated with non-consented vaginal examinations (AOR 2.3, 1.7–3.1) and poor communication (AOR 2.0, 1.3–3.2). In Nigeria, it was associated with longer wait times (AOR 0.6, 0.3–0.9). Conclusion: Labour companionship is associated with lower levels of some forms of mistreatment that women experience during childbirth, depending on the setting. Further work is needed to ascertain how best to implement context-specific labour companionship to ensure benefits while maintaining women's choices and autonomy.